The Impact of Child Support Receipt on Household Income and Labour Supply - Fisher, Hayley (Sydney, 2015)
International evidence suggests that child support schemes provide a small but signif- icant contribution to the household income of lone parents and have modest success in reducing child poverty. There are, however, concerns that receiving child support may discourage labour force participation. I use data from the Household, Income and Labour Dynamics in Australia (HILDA) survey to estimate the effect of receiving child support on government transfer receipt, earned income, hours worked and labour force participation of eligible mothers. OLS estimates of the effect of receiving child support on household behaviour may be biased as a mother’s income partly determines the level of support received, and due to the interaction of child support with government transfers. I exploit information about the employment status of a child’s non-resident father and find that receiving any child support is associated with a reduction in government transfers, an increase in earned income, and an increase in household income in excess of the amount of child support received. Mothers receiving child support are more likely to be in full time employment, work more hours per week, and are less likely to be out of the labour force.
Economics Working Paper Series
Keywords: Benefits and Payments -- Child support; Income, wealth and finances; Benefits and Payments; Child support; Income, wealth and finances